Clinicopathological characterization of children with dysphagia, family impact and health-related quality of life of their caregivers - Pilar Ortiz Pérez; Inés Valero Arredondo; Encarnación Torcuato Rubio; Andrés Rosa López; Pascual García-Herrera Taillifer; Víctor Manuel Navas-López (Elsevier, 2022)
Introduction: Oropharyngeal dysphagia (DOF) without proper evaluation can be underdiagnosed in certain groups of the pediatricpopulation. Meeting the needs of these patients can lead to an overload of their caregivers. Objectives: To describe the epidemiological and clinical characteristics of the patients evaluated after starting a monographic DOF clinic (C-DOF) and study whether there are changes at the nutritional level, as well as the burden and impact that caregivers find on quality of life related to health (HRQL). Material and methods: Descriptive observational study of patients evaluated in a C-DOF from its start-up. To evaluate HRQoL, an ad hoc survey adapted from the Swallowing Quality of Life Questionnaire of the adult population was designed. Results: 103 patients were evaluated, 85.4% presenting some neurological disease. A videofluoroscopic study was performed in 51 patients (49.5%), reporting combined alterations in both the oral and pharyngeal phases in 64.7% of them. There was a directly proportional correlation between the severity of the DOF and the presence of aspirations, as well as with the patient's motor impairment. Regarding the anthropometric evaluation, there was a trend towards improvement in weight z-score (+0.14 SD), height (+0.17 SD) and BMI (+0.16 SD). Out of 46.2% of the caregivers reported that the DOF problem interfered negatively in the basic activities of daily life. The increase in HRQOL, after the evaluation in the monographic DOF clinic, was statistically significant overall. Conclusions: The monographic DOF clinic provided specialized care, impacting positively at the nutritional status of patients, as well as perceived changes in HRQOL, with a probable impact on caregivers. Resumen: Introducción: La disfagia orofaríngea (DOF) puede resultar infradiagnosticada en determinados grupos de población pediátrica. Atender las necesidades de estos pacientes puede derivar en una sobrecarga de sus cuidadores. Objetivos: Describir las características epidemiológicas y clínicas de los pacientes evaluados tras la creación de una consulta monográfica de DOF (C-DOF), estudiar cambios a nivel nutricional, así como la repercusión en la calidad de vida relacionada con la salud (CVRS) de los cuidadores. Material y métodos: Estudio observacional descriptivo de los pacientes evaluados en una C-DOF desde su puesta en marcha. Para evaluar la CVRS, se diseña una encuesta ad hoc adaptada del Swallowing Quality of Life Questionnaire de población adulta. Resultados: Se evaluaron 103 pacientes (85,4% con patología neurológica de base). Se realizó estudio videofluoroscópico a 51 pacientes (49,5%), reportando alteraciones combinadas de fase oral y faríngea un 64,7%. Existió una correlación directamente proporcional entre la gravedad de la DOF y la presencia de aspiraciones, así como con la afectación motora del paciente. En cuanto a la evaluación antropométrica, se observó mejoría en z-score de peso (+0,14 DE), de talla (+ 0,17 DE) y de IMC (+ 0,16 DE). El 46,2% de los cuidadores refirieron que la DOF interfiere negativamente en las actividades básicas de la vida diaria. El incremento en calidad de vida, tras la evaluación en la C-DOF, de forma global resultó estadísticamente significativo. Conclusiones: La C-DOF proporciona una atención especializada, repercute positivamente en el estado nutricional de los pacientes, así como en los cambios percibidos en la CVRS, con probable impacto en los cuidadores.